Stand-off LIBS for steel-grade intermix detection in sequence casting operations. At-line monitoring of temporal evolution vs predicted mathematical model - Cabalín-Robles, Luisa María; Delgado-Pérez, Tomás; Ruiz-del-Castillo, Javier; Mier, D.; Laserna-Vázquez, José Javier (Elsevier, 2018)
Continuous casting is an extensively used industrial process for steel manufacturing. In this common method of steel production, forms (billet/bloom/slab) involving a change of steel grade present a variation in elemental composition from the first heat to the second one. In a previous work, the capabilities of dual-pulse stand-off laser-induced breakdown spectroscopy (LIBS) to detect the separation between grades for stainless steel slabs have been demonstrated. In that case, Cr and Mo were the elements allowing this intermixing detection. In the current work, this LIBS system has been optimized and mounted at 3.6 m from hot billet in the continuous casting line in the Sidenor steel factory in Basauri, Bilbao (Spain), ahead the oxycutting unit, in order to discriminate between billets of special steel, where typical scale layer thicknesses are in the order of 100–400 μm. In this challenging case (due to the formation of a much thicker oxidized layer), minor elements as Pb (change from nill to 0.17%) or V (from nill to 0.1%) have proved to be useful for detection of the grade transition. After the experiment, laboratory LIBS measurements were carried out on small pieces cut from a selected billet where the intermixing was detected at-line, confirming the experimental results obtained in factory. Both laboratory and at-line LIBS information are in agreement with the chemical composition determined by optical emission spectroscopy (OES), and with the results of a mathematical model predicting the temporal evolution of the elemental content in the intermix region.
Keywords: Colada continua; Espectroscopía de plasma inducido por láser; Remote LIBS; Scale layer; Discriminant function analysis; Continuous casting manufacturing; Grade transition